2022
DOI: 10.33555/jffn.v4i1.96
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Glutinous Rice Tape Added with Lactobacillus plantarum Dad-13 and Saccharomyces boulardii as a Probiotic Food

Wisnu Adi Yulianto,
Dwiyati Pujimulyani,
Candrika Ayu Pratami

Abstract: Glutinous rice tape circulating in the community generally does not contain probiotic cells. However, adding Lactobacillus plantarum Dad-13 and Saccharomyces boulardii can increase its potential as a probiotic food. This study is aimed to determine the effect of using glutinous rice varieties and the addition of probiotic cells on the number of lactic acid bacteria (LAB) and yeast, levels of anthocyanins, antioxidant activity, as well as the preference level of glutinous rice tape produced. A completely random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This may be influenced by the use of probiotics in microencapsulated form with skim milk coating that can play role in maintaining stability from damage caused by processing involving hot temperatures, storage, and bile salts (Jati et al, 2015). Research conducted by Yulianto et al (2022) also showed the addition of L. plantarum Dad-13 on black and white glutinous race tapes could increase the amount of LAB up to 2 log cycles from 6 to 8 log CFU/g, which qualifies minimum LAB content for probiotic food.…”
Section: Total Lactic Acid Bacteria (Lab)mentioning
confidence: 93%
“…This may be influenced by the use of probiotics in microencapsulated form with skim milk coating that can play role in maintaining stability from damage caused by processing involving hot temperatures, storage, and bile salts (Jati et al, 2015). Research conducted by Yulianto et al (2022) also showed the addition of L. plantarum Dad-13 on black and white glutinous race tapes could increase the amount of LAB up to 2 log cycles from 6 to 8 log CFU/g, which qualifies minimum LAB content for probiotic food.…”
Section: Total Lactic Acid Bacteria (Lab)mentioning
confidence: 93%